The effect of celery ethanol extract (Apium graveolens l.) against fatty liver in rat model of hyperlipidemia - Trimurtini, Indarti; Pradini, Astri; Vita Nirmala Sari, Vania; Sovia, Evi (ACTA Medical Health Sciences, 2023)
Fatty liver is a disorder of liver characterized by the accumulation of fat liver cells. The incidence of fatty liver in Indonesia is 30%. Fatty liver can be caused by hyperlipidemia. Hyperlipidemia triggers an increase of oxidative stress that leads to fatty liver. Treatment is usually carried out using statins, but long-term consumption of statin may lead to several side effects. Other treatment that can lower cholesterol levels traditionally is celery. This study aimed to determine the effect of ethanol extract of celery on the microscopic appearance of the liver induced by hypercholesterolemia in experimental rats. This was an posttest control group experimental on 25 rats that were divided into 5 groups: negative control group, positive control group, and three (3) treatment groups. Each treatment group was given a high-fat diet for 14 days, followed by a provision of high-fat diet with different celery extract doses of 37.5 mg/KgBW/day, 75 mg/KgBW/day, and 150 mg/KgBW/day. After the treatment completed, the rats were sacrificed and dissected, and their liver was for histopathological preparations. Data on the in the average fat score between the control group and the three treatment groups were collected and analyzed using one way ANOVA if they were normally distributed with the Kruskal Wallis test as the alternative test. To determine whether there was a significant difference between two treatment groups, a post-hoc statistical test was performed. A significant change was observed in the histological presentations of the liver between control and treatment groups (p <0.5). There was a marked improvement of cytoplasm, sinusoid and cell nucleus in the treatment groups compared to positive control group with a dose of 37.5 mg/KgBW/day as the most effective celery ethanol extract to improve liver fat due to fat accumulation. DOI : 10.35990/amhs.v1n3.p121-127 REFERENCES Wulandari RL, Susilowati S, Murnik A. Pengaruh kombinasi ekstrak etanol daun sirsak (Annona muricata) dan simvastatin terhadap kadar kolesterol total dan Low Density Lipoprotein (LDL) tikus yang diinduksi pakan tinggi lemak. Hiperkolesterol, Ekstrak Etanol Daun Sirsak, Koles Total LDL. 2015;(LDL):24–32. Syafitri V, Arnelis A, Efrida E. Gambaran profil lipid pasien perlemakan hati non-alkoholik. J Kesehat Andalas. 2015;4(1):274–8. Yao YS, Li TD, Zeng ZH. Mechanisms underlying direct actions of hyperlipidemia on myocardium: An updated review. Lipids Health Dis. 2020;19(1):1–6. Setiawan SI, Kurniawan J, Bhakti Asih R, Tangerang K, Hepatobilier D. Pilihan tatalaksana penyakit perlemakan hati non-alkohol (Non-Alcoholic Fatty Liver Disease/NAFLD). Cermin Dunia Kedokt. 2021;48(3):173–5. Chitturi S, Farrell GC, Hashimoto E, Saibara T, Lau GKK, Sollano JD. Non-alcoholic fatty liver disease in the Asia-Pacific region: Definitions and overview of proposed guidelines. J Gastroenterol Hepatol. 2007;22(6):778–87. Neuschwander-Tetri BA. Non-alcoholic fatty liver disease. BMC Med. 2017;15(1):1–6. Oktavianie DA. Hiperkolesterolemia, benalu mangga, trigliserida, histopatologi hepar. Laporan Penelitian. Fakultas Kedokteran Universitas Halu Oleo; 2020:1–8. Sanchez P, Chetty G, Sarkar P. Not the typical winter cough. BMJ Case Rep. 2009. Guyton AC, Hall JE. Buku Ajar Fisiologi Kedokteran. Edisi ke-12. Jakarta: ECG; 2006. Hariadini AL, Sidharta B, Ebtavanny TG, Minanga EP. Hubungan tingkat pengetahuan dan ketepatan penggunaan obat simvastatin pada pasien hiperkolesterolemia di apotek kota Malang. Pharm J Indones. 2020;5(2):91–6. Hartono H, Handayani S. Pengaruh pemberian seledri (Apium graveolens) terhadap penurunan hiperkolesterolemia pada lansia di Panti Wreda Darma Bhakti Kasih Surakarta. Interes J Ilmu Kesehat. 2017;6(2):217–23. Handayani L, Widowati L. Analisis lanjut pemanfaatan empiris ramuan seledri (Apium graveolens) oleh penyehat tradisional. J Kefarmasian Indones. 2020;31–41. Yao Y, Sang W, Zhou M, Ren G. Phenolic composition and antioxidant activities of 11 celery cultivars. J Food Sci. 2010;75(1):9–13. Susanti R, Yuniastuti A. Efektivitas ekstrak tanin seledri terhadap profil lipid tikus putih hiperkolesterolemia. Life Sci. 2012;1(2). Rusdiana T. Telaah tanaman seledri (Apium graveolens) sebagai sumber bahan alam berpotensi tinggi dalam upaya promotif kesehatan. Indones Nat Res Pharm J. 2018;3(1):1–8. Priatna RD. Efek anti-hiperkolesterolemia ekstrak etanol daging buah plum (Prunus salicina) pada tikus jantan galur Wistar yang diinduksi diet tinggi lemak. Tesis. Universitas Jenderal Achmad Yani; 2020. Kleiner DE, Brunt EM, Van Natta M, et al. Design and validation of a histological scoring system for nonalcoholic fatty liver disease. Hepatology. 2005;41(6):1313–21. Badan Pengawas Obat dan Makanan Republik Indonesia. Acuan Sediaan Herbal. BPOM RI; 2020:1–58. Sunarjono H. Bertanam Sayuran Daun & Umbi. Jakarta: Penebar Swadaya Grup; 2018. Pujiwidodo D. Formularium Obat Herbal Asli Indonesia. Vol. III. Jakarta: Kementerian Kesehatan RI; 2016.